MODERN SOLUTIONS FOR THE USE OF ANTICOAGULANTS IN MYOCARDIAL INFARCTION AND ARRHYTHMIAS - H.N, Turayev; Kholmurodovich, Khurramov Bobir (PT. Antis International Publisher, 2025)
Objective: This study aims to explore the causes, symptoms, diagnostic methods, and treatment strategies for acute myocardial infarction (AMI), focusing on the role of coronary artery obstruction in its development and the available therapeutic options. Methods: Diagnosis of AMI is based on electrocardiography (ECG) and biomarker analysis. Treatment protocols include the administration of antiplatelet agents, anticoagulants, nitrates, beta-blockers, statins, and various reperfusion therapies. The study also examines the use of fibrinolytic drugs, percutaneous interventions, and coronary artery bypass grafting (CABG) in different types of AMI. Results: Acute myocardial infarction presents with symptoms such as shortness of breath, nausea, chest discomfort, and sweating. Diagnosis is confirmed through ECG readings and biomarker testing. Effective treatment varies based on the severity and type of AMI, with reperfusion therapy being critical for ST-segment elevation myocardial infarction (STEMI), while non-ST-segment elevation myocardial infarction (NSTEMI) may require percutaneous intervention or CABG. Novelty: This study contributes to understanding the nuanced diagnostic and therapeutic approaches to AMI, particularly in differentiating treatment strategies for STEMI and NSTEMI, highlighting the importance of timely and appropriate interventions for improving patient outcomes.